Conflict Management of Indonesian Students in China From the Perspective of Face-Negotiation Theory - Nafisa Nugraheni Sania Putri; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2024)
Indonesian students who study in China often face challenges when trying to adapt, including cultural misunderstandings with their friends or lecturers. As a result, they need to effectively handle conflicts to address these issues. They endure culture shock as a result of a highly efficient payment system, an immaculately clean environment, and other extremely practical features. The differences in natural environment are also a factor in different cultures of environment. This research examines how Indonesian students, who encounter difficulties in China manage conflicts related to their intercultural experiences, using the Face Negotiation Theory as a perspective. This study uses descriptive qualitative with a case study method. Data was obtained through interviews with three Indonesian students studying in Chinese universities. The findings indicate that cultural differences and habits contribute to misunderstandings between Indonesian and Chinese students. This research reveals that Indonesian students use avoiding and compromising as conflict management strategies when resolving intercultural communication issues.